2018
DOI: 10.1007/s10157-018-1567-1
|View full text |Cite
|
Sign up to set email alerts
|

Independent regulation of renin–angiotensin–aldosterone system in the kidney

Abstract: Renin–angiotensin–aldosterone system (RAAS) plays important roles in regulating renal hemodynamics and functions, as well as in the pathophysiology of hypertension and renal disease. In the kidney, angiotensin II (Ang II) production is controlled by independent multiple mechanisms. Ang II is compartmentalized in the renal interstitial fluid with much higher concentrations than those existing in the circulation. Inappropriate activation of the intrarenal RAAS is an important contributor to the pathogenesis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 96 publications
1
92
0
Order By: Relevance
“…A suppressed systemic renin-angiotensin system is commonly seen in subjects with salt-dependent hypertension [29]. Consistently, we have shown that HSD-fed DSS rats exhibit a marked decrease in plasma angiotensin II levels, accompanied by reduced plasma renin activity (PRA) [30,31]. Therefore, the reduced RAS activity may not contribute to the pathogenesis of the dipping pattern of BP in HSD-fed DSS rats.…”
Section: Discussionsupporting
confidence: 53%
“…A suppressed systemic renin-angiotensin system is commonly seen in subjects with salt-dependent hypertension [29]. Consistently, we have shown that HSD-fed DSS rats exhibit a marked decrease in plasma angiotensin II levels, accompanied by reduced plasma renin activity (PRA) [30,31]. Therefore, the reduced RAS activity may not contribute to the pathogenesis of the dipping pattern of BP in HSD-fed DSS rats.…”
Section: Discussionsupporting
confidence: 53%
“…Renin–angiotensin system is known best for its role in the maintaining a balance of blood pressure, electrolyte and fluid homeostasis (Nishiyama & Kobori, ; Sparks et al, ). Nevertheless, the actions of the RAS reach beyond the scope of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Renin–angiotensin system is mainly a blood‐borne hormone system, which regulates blood pressure, electrolyte and fluid homeostasis (Nishiyama & Kobori, ; Sparks, Crowley, Gurley, Mirotsou, & Coffman, ; Te Riet, Esch, Roks, Meiracker, & Danser, ). Intrinsic RAS exists in numerous tissues, which can adapt to specific local needs by adding to or differing from the circulating RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate RAS activation is crucial in the development of cardiovascular disease and chronic kidney disease (CKD) associated with diabetes [ 31 ]. In response to declining renal perfusion pressure and sodium delivery to distal tubules, juxtaglomerular cells markedly increase renin secretion [ 32 ]. SGLT2i can cause natriuresis in the early phase of treatment, which may activate systemic RAS.…”
Section: Hemodynamic Factors Affected By Sglt2imentioning
confidence: 99%